Sandy Everlasting (Helichrysum arenarium (L.) Moench): Botanical, Chemical and Biological Properties - Pljevljakušić, Dejan; Bigović, Dubravka; Janković, Teodora; Jelačić, Slavica; Šavikin, Katarina (Frontiers in Plant Science, 2018)
Sandy everlasting [Helichrysum arenarium (L.) Moench] is herbaceous perennial plant belonging to Asteraceae family and it is native to Europe, Central Asia, and China. It belongs to the section HELICHRYSUM (Asteraceae family, genus Helichrysum) along with H. plicatum DC. Prodr., which very similar phenolic profile and H. italicum (Roth), which is widely used for essential oil extraction. Its flowers have a long tradition in European ethnomedicine as a cholagogue, choleretic, hepatoprotective, and detoxifying herbal drug. The flowers are rich in phenolic compounds including flavonoids, chalcones, phenolic acids, coumarins, and pyrones. Apart from polyphenols, other compounds such as sterols, lignans, and glycosides of aromatic compounds have been also isolated from H. arenarium. The majority of authors confirm that the most important group of compounds responsible for biological activities is flavonoids. Moreover, significant activities of naringenin, one of the main flavonoids of H. arenarium, were reported. On the other hand, there are no clinical data about testing the extracts or preparations based on H. arenarium. Although H. arenarium is well known in phytotherapy for its potential in the treatment of gallbladder disease and are classified as endangered species in a number of European countries, very few data about its cultivation are available in the literature.